METHODOLOGICAL FRAMEWORK FOR GOVERNMENTAL ASSISTANCE TO AGRICULTURAL ENTERPRISES THROUGH INNOVATIVE MANAGEMENT TECHNIQUES (American Journal of Pedagogical and Educational Research, 2024)
This article explores the scientific and methodological approaches to state support for agricultural enterprises, focusing on the integration of innovation management principles. The article emphasizes the importance of utilizing innovation management strategies to improve agricultural productivity, efficiency, and competitiveness. By examining different approaches and frameworks for innovation, the article offers recommendations on how the state can better support agricultural enterprises through targeted policies, investments in research and development (R&D), and the promotion of digital technologies. The article also highlights indicators for evaluating the effectiveness of state support in this area.